PERAN INTELEGENSI DAN BAKAT DALAM PEMBELAJARAN - jufri, Jufrizal (Jurnal Tarbiyah Almuslim, 2024)
This research is library research, namely research that uses data sources from library searches in the form of the Koran, books and articles as the main source. This research is qualitative research with a rationalistic approach as the basis for collecting data. Data collection techniques use documentation as a reference in research. The research results obtained: First, Ta'dib, describes the process of character formation and manners. This involves the teacher's efforts to guide students in developing noble morals, providing examples, advice and guidance, creating people who believe and have good morals according to Islamic teachings. Second, Ta'lim, emphasizes the cognitive aspect of learning, providing the knowledge and skills needed in life, as well as guidelines for good behavior. Ta'lim strengthens the connection between teaching and learning by conveying clear and structured messages. Third, Tarbiyah, refers to the process of coaching and developing individuals as a whole. This includes the development of faith, knowledge, and charity, which are interrelated and important in achieving educational goals. Tarbiyah creates Muslim individuals who are ready to lead the people in the future with wisdom and courage. By applying this concept holistically, Islamic education can become the main pillar in building a generation that is devout and has noble morals.